Menghadapi Zaman Millennial Melalui Jero Dasaran Dalam Menanamkan Pendidikan Karakter Di Desa Songan A dan B, Kintamani, Bangli - Gede Rai Parsua (Guna Widya: Jurnal Pendidikan Hindu, 2022)
In this millennial era, technology is growing rapidly. Gadgets and the internet also seem to have become the daily habits of the millennial generation. The current millennial generation is filled with teenagers, adults who now act as children, school students, university students. Jero Dasaran is determined or appointed by means of Ngerawang or generally outside the village of Songan is called nyanjan, which aims to serve or to ngayah in one of the temples that are the sungsungan for the Songan community, for example in the Village Temple, Hulundanu Temple and others. The formulation of the problem proposed is; What is the role of Jero Dasaran in instilling character education to face the millennial era in Songan A and B Villages, Kintamani, Bangli ? What is the meaning of Jero Dasaran in instilling character education to face the millennial era in Songan A and B Villages, Kintamani, Bangli ? What are the implications of Jero Dasaran in instilling character education to face the millennial era in Songan A and B Villages, Kintamani, Bangli ? Data collection methods used : moderate participatory observation, unstructured or in-depth interviews, literature, documentation. The role of Jero Dasaran in Songan is as a young generation, as the successor because there are so many Jero Dasaran and most of them are still teenagers. The role of Jero Dasaran is very much needed in instilling character education because every time there is a religious moment, the socio-religious in Songan always presents Jero Dasaran, automatically Jero Dasaran is an example in daily life behavior. The meaning of Jero Dasaran; The meaning of devotion, the meaning of togetherness, the meaning of ethical education, the meaning of being diligent in working because being Jero Dasaran must be an example for other millennials, because some of the Songan community are farmers, as a whole in Songan the environment is still sustainable, this can be seen that most of the Songan village area is a garden For agriculture, almost no agricultural land is turned into concrete and it is very rare for the land of the Songan people to be sold to people outside Songan.The implications of the formation of Jero Dasaran to face the millennial era in instilling character education in the villages of Songan A and B, Kintamani, Bangli is more diligent in praying, interacting more frequently with the community and cannot be separated from Catur Purusa Arta